2015
DOI: 10.1080/09507116.2014.937618
|View full text |Cite
|
Sign up to set email alerts
|

Weldability of high strength steel in underwater environment

Abstract: The article describes the problems with weldability of high-strength steels in the aquatic environment. The tendency of steel S355J2G3 and S500M to form cold cracks when welded in wet welding conditions has been experimentally evaluated.It was found that the tested steels have a high propensity to cracking. An experiment has been proposed and tested to evaluate the usefulness of the tempering bead technique as a method of improving the weldability of high-strength steels under water in wet welding conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…They concluded that rapid cooling rate can improve the impact toughness and tensile strength of weld metal in local dry underwater welding. Fydrych et al [ 7 ] studied the weldability of high strength steel in underwater environment. They concluded that joints of steel S355J2G3 and S500M created underwater in conditions of restraint showed a strong tendency to form cold cracks in the weld.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that rapid cooling rate can improve the impact toughness and tensile strength of weld metal in local dry underwater welding. Fydrych et al [ 7 ] studied the weldability of high strength steel in underwater environment. They concluded that joints of steel S355J2G3 and S500M created underwater in conditions of restraint showed a strong tendency to form cold cracks in the weld.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the fillet break tests of the fillet T SD(A)-2F-130A and fillet T SD(A)-2F-160A specimens are presented in Figure 5, revealing specimens with incomplete penetration (IP), lack of fusion (LF), and slag inclusions (SI) that are not acceptable for class A and B welds, according to AWS D3.6 [10] and the previous studies conducted by Civjan S.A. et al [33] and Amirafshari P. et al [34]. However, the welds conform to the ARC requirements for this research work and the welder's experience.…”
Section: Characterization Of Uww Fillet Jointsmentioning
confidence: 99%
“…It is crucial to assess the impact of heat input on the weldability and mechanical properties of steels welded using the UWW method. In a study conducted by Jiajing Pan et al [9] on the weldability of E36 steel in underwater conditions, it was observed that the HAZ near the weld metal undergoes a complete transformation into lath martensite and exhibits increased hardness; in addition, Dariusz Fydrych et al [10] described the weldability challenges of high-strength steels (HSS), such as cold cracking, and proposed an experiment to evaluate the bead tempered technique as an improvement in weldability of these steels in UWW conditions, obtaining that the bead tempered technique reduces the maximum HAZ hardness from 400 HV10 to less than 350 HV10, which demonstrates the suitability of the bead tempered technique for welded joints of HSS. Meanwhile, Zahit Çolak et al [11] performed welded joints of ASTM A131 AH36 steel using atmospheric SMAW, UWW-SMAW with casing-isolated electrodes at 8 m depth, and E6013 and E7024 electrodes to evaluate and compare the mechanical and metallurgical properties of welded joints.…”
Section: Introductionmentioning
confidence: 99%